Membangun Citra Madrasah: Strategi MTs. Al-Kautsar Dalam Membangun Mutu - Edy Susanto (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2019)
This article aims to describe the efforts made by the Al-Kautsar Ranggo Mts School to build quality with a strategy to build quality. The type of research used in qualitative research is in the form of research procedures that produce descriptive data. In collecting data, researchers used the method of observation, documentation, and research interviews conducted at MTs. Al-Kautsar Ranggo. The results of the above research indicate that the efforts made by MTs. Al Kautsar Ranggo in building an image to build quality is to increase MTs. Al-Kautsar Ranggo Human Resources (HR) Educators and Education Personnel, Curriculum Development, Learning and Achievement of MTs Students. Al-Kautsar Ranggo developed the Quality Concept of MTs. Al-Kautsar Ranggo and Socialization of MTs Public Relations. Al-Kautsar Ranggo